SYBR Green real-time qPCR method: Diagnose drowning more rapidly and accurately. (April 2021) - Yu, Zhonghao; Xu, Quyi; Xiao, Cheng; Li, Huan; Wu, Weibin; Du, Weian; Zhao, Jian; Liu, Hong; Wang, Huijun; Liu, Chao
Highlights: ● 6 pairs of primers were designed. ● SYBR Green real-time qPCR was applied. ● standard strains and forensic cases were verified. were used to verify the sensitivity and specificity of the primes, results showed the detection range could reach 0.0001 ng; forens. Abstract: In the field of drowning research, the method of diatom morphology has been most applied to determine whether the cause of death is drowning. However, the characteristics of complex operation, high level of professional knowledge drive us to propose a new method. Here, based on the common phytoplankton in water(such as diatoms and Aeromonas), aiming at the rbc L, 23 S, NIES, rPOD, Hly and preprotoxin aerolysin gene, we designed 6 pairs of specific primers and applied SYBR Green real-time qPCR(RT-qPCR) method to detect phytoplankton in the Pearl River Basin of Guangdong Province, China, so as to achieve the purpose of diagnosing drowning. After the experimental verification of the corresponding algae species and the standard strains of bacteria, as well as the verification of tissue samples (lung, liver and kidney) of 56 cases( 40 drowning cases and 16 non-drowning cases), we found that these primers were of great accuracy and tedious laboratory work of diatom test was reduced. Based on the advantages of high throughput, short period and high sensitivity, this RT-qPCR method is expected to diagnose drowning more rapidly and accurately.